Identificação de comorbidades e fatores de risco cardiovascular em pacientes portadores de psoríase - Isabela Guimaraes Ribeiro (2013)
INTRODUCTION: Psoriasis is a immune-mediated, chronic inflammatory disease that affects 1-3% of the general population. Its pathogenesis involves a complex interaction of genetics, environmental exposures and the immune system. Recent studies suggest that the chronic inflammatory nature of psoriasis may predispose to other diseases with an inflammatory component, notably cardiovascular and metabolic disorders. OBJECTIVES: To describe the demographic, clinical, epidemiological and laboratorical characteristics of a sample of psoriatic patients; to evaluate the prevalence of clinical comorbidities, cardiovascular risk factors and metabolic syndrome; to correlate data with the severity of psoriasis and to identify the cardiovascular risk profile based on the Framingham Risk Score.METHODS: A cross-sectional study was performed, and 190 patients were evaluated between July 2011 and May 2012. Patients were submitted to anamnesis and physical evaluation, and responded a questionnaire about epidemiological data, previous pathological history and presence of comorbidities. Laboratory data were collected from the patients´ medical records. The cardiovascular risk profile was calculated by the Framingham risk score and metabolic syndrome was defined according to National Cholesterol Education Program -Adult Treatment Panel III (NCEP-ATP III) criteria. As to statistical analysis the chi-square test was used to comparison of proportions, the student´s t-test was used to compare means and for variables which did not have Gaussian distributions was used the Kruskal-Wallis test to comparison of medians. For independent association, the statistical significance was established as p < 0.05. RESULTS: In this sample, the mean age was 51.5 ± 14 years, with similar proportion between genders. Plaque psoriasis was the most frequent form of psoriasis (78.4%). Nail involvement was found in 62.1% of the patients, and 19.5% had previous diagnostic of psoriatic arthritis. We found increased prevalence of systemic arterial hypertension, diabetes mellitus, metabolic syndrome and obesity in our patients, especially if compared with general population. High abdominal circumference measurement was reported, besides considerable prevalence of depression and regular alcohol intake. The association with smoking was described, with mean of pack-years of 21.3 ±16 years, which is considered high tobacco smoking load. According to the severity criteria that were used, severe psoriasis was detected in 67.4% of the patients. The patients with body mass index 25 had the tendency of presenting severe psoriasis. The patients´ cardiovascular risk was high by the Framingham score: 47.2% of the patients had medium or high ten-year risk of fatal and non-fatal cardiovascular events. The Framingham score means was 10.5 ± 9.1, and is considered high if compared with other studies involving Brazilian population. There was statistical significance related to gender, with male having higher Framingham score. CONCLUSIONS: The patients had high prevalence of cardiovascular comorbidities such as systemic arterial hypertension, diabetes mellitus, metabolic syndrome and obesity, and also a high cardiovascular Framingham score. Those associated comorbidities increase the disease´s morbidity and mortality rates. Therefore, it should be empathized the importance of preventive measures and earlier and effective treatment. Further studies in our country are necessary for validation of the results.